2020
DOI: 10.48550/arxiv.2012.05627
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

X-ray Plateaus in Gamma-Ray Burst Afterglows and Their Application in Cosmology

Fan Xu,
Chen-Han Tang,
Jin-Jun Geng
et al.

Abstract: For gamma-ray bursts (GRBs) with a plateau phase in the X-ray afterglow, a so called L-T-E correlation has been found which tightly connects the isotropic energy of the prompt GRB (E γ,iso ) with the end time of the X-ray plateau (T a ) and the corresponding X-ray luminosity at the end time (L X ). Here we show that there is a clear redshift evolution in the correlation. Furthermore, since the power-law indices of L X and E γ,iso in the correlation function are almost identical, the L-T-E correlation is insens… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Interestingly, some works have shown that long GRBs can be potentially used to extend the Hubble diagram out to high redshifts (Frail et al 2001;Dai et al 2004;Ghirlanda et al 2004b,a;Schaefer 2007;Liang & Zhang 2005). However, due to the diversity of light curves, a reliable method to standardize them has not yet been established, though recent work provides encouraging results (Cardone et al 2009;Dainotti et al 2013b;Postnikov et al 2014;Wang et al 2016;Demianski et al 2017;Amati et al 2019;Fana Dirirsa et al 2019;Tang et al 2019;Xu et al 2020;Muccino et al 2021;Khadka et al 2021).…”
mentioning
confidence: 99%
“…Interestingly, some works have shown that long GRBs can be potentially used to extend the Hubble diagram out to high redshifts (Frail et al 2001;Dai et al 2004;Ghirlanda et al 2004b,a;Schaefer 2007;Liang & Zhang 2005). However, due to the diversity of light curves, a reliable method to standardize them has not yet been established, though recent work provides encouraging results (Cardone et al 2009;Dainotti et al 2013b;Postnikov et al 2014;Wang et al 2016;Demianski et al 2017;Amati et al 2019;Fana Dirirsa et al 2019;Tang et al 2019;Xu et al 2020;Muccino et al 2021;Khadka et al 2021).…”
mentioning
confidence: 99%
“…The discovery of the 2D Dainotti relation in X-rays marked the first time an afterglow correlation had been used as a cosmological tool (Cardone et al 2009(Cardone et al , 2010Dainotti et al 2013b;Postnikov et al 2014). The 2D correlation in X-rays has been interpreted within several models such as the accretion onto the black hole (Cannizzo & Gehrels 2009, as powered by a fast spinning neutron star (Rowlinson et al 2013(Rowlinson et al , 2014Stratta et al 2018;Cao et al 2021aCao et al , 2022Hu et al 2021;Wang et al 2021a;Xu et al 2020) or as a modification of the microphysical parameters models (Leventis et al 2014;van Eerten 2014a,b;Varela et al 2016) which consider jets viewed slightly off-axis (Beniamini et al 2020). Although these works deal strictly with the Dainotti relation in X-ray, recently it has been found that there exists also a two-dimensional relationship in optical wavelengths for a sample of 102 GRBs between the optical rest-frame end time, 𝑇 OPT , and the optical luminosity at the end of the plateau, 𝐿 OPT (Dainotti et al 2020b).…”
mentioning
confidence: 99%